PERAN PENTING SISTEM INFORMASI DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Salsabila, Ti'Laili; Hidayati, Dian; Zuhaery, Muhammad (STKIP Pesisir Selatan, 2025)
Good quality education will have a positive impact on the development of individuals and society as a whole. However, to achieve the desired quality of education, an effective system is needed in managing educational information. One system that can play an important role in improving the quality of education is the Management Information System. This study aims to examine the role of information systems in improving the quality of education, especially in these primary schools. The research method used is a descriptive qualitative approach with data collection techniques through observation and interviews with teachers. The results showed that information technology management has seven main roles in supporting the improvement of education quality, namely information system integration, improving teacher performance, administrative support, developing digital competencies, and improving teaching quality. The implementation of information systems in schools helps teachers in managing administrative tasks, providing more interactive learning resources and improving the effectiveness of communication between teachers, students and parents. The conclusion of this study confirms that a well-implemented management information system can contribute to improving the overall quality of education.